Public Values Kebijakan Relokasi Pasar Kota Bojonegoro - Novianti, Salsa Bella Nurikma; Suprastiyo, Ahmad; Kasiami, Sri (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The market relocation policy aims to meet the economic needs or interests of the community and is related to better development. The government as a public service seeks to create good public value for society. As in this research, the aim is to describe the public value of the Bojonegoro City Market relocation policy. The research was conducted using descriptive qualitative research methods, with data collection techniques in the form of observation, interviews and documentation. This research focuses on Mark Moore's public value theory, including: legitimacy and support, operational capabilities, and substantively valuable. The results of this research indicate that the Bojonegoro City Market relocation policy has largely fulfilled Mark Moore's public value theory. It's just that at the beginning of the implementation of the policy, it received resistance from Bojonegoro City Market traders because it affected their income. As time went by, traders switched to the Tourism Market and felt the benefits tourists. Even traders' income increased by up to 50%. Supported by adequate facilities, people feel comfortable, safe and enthusiastic about shopping at the Tourism Market.